Factors Associated with SARS-CoV-2 Infection before Vaccination among European Health Care Workers - Mansour, Ihab; Godono, Alessandro; Sansone, Emanuele; Visci, Giovanni; Spiteri, Gianluca; Lourdes Monaco, Maria Grazia; Mates, Dana; Rascu, Agripina; Duval, Xavier; Pira, Enrico; Ciocan, Catalina; Violante, Francesco; et al. (La Medicina del Lavoro, 2023)
Background: Health care workers (HCWs) were on the frontline of the current pandemic. We aimed at identifying determinants of SARS-CoV-2 infection and the effectiveness of personal protection equipment (PPE) worn by HCWs before vaccination. Methods: We abstracted data on SARS-CoV-2 infection based on positive PCR results and sociodemographic characteristics of 38,793 HCWs from public hospitals and public health authorities from 10 European centers. We fitted cohort-specific multivariate logistic regression models to identify determinants of infection and combined the results using random-effects meta-analyses. Results: The overall prevalence of infection before vaccination among HCWs was 9.58%. Infection was associated with the presence of selected symptoms; no association was found between sociodemographic factors and increased risk of infection. The use of PPE and particularly FFP2/FFP3 masks had a different protective effect during the first and second waves of the COVID pandemic. Conclusions: The study provides evidence that mask use was the most effective PPE in preventing SARS-CoV-2 infection among HCWs.